Respuesta :

Answer:

y = 5

Step-by-step explanation:

1/3(y+7)=3(y-1)

Multiply the entire equation by 3 to rid of fractions

3(y+7) = 9(y-1)

Distribute over brackets

3y + 21 = 9y - 9

Combine like terms over both sides

30 = 6y

Divide both sides by 6

5 = y

y = 5 (variable on left side is standard)

Answer: y=2

Step-by-step explanation:

1/3(y+7) = 3(y-1)  

simplify to 1/3y + 7/3 = 3y - 3

                          -7/3          -7/3

———————————-——————

1/3y = 3y - 16/3

-3y     -3y

—————-——————-—

-8/3y = -16/3

divide both sides by -8/3

y=2